Left Main Coronary Stenosis as a Consequence of Bentall Operation: Percutaneous Treatment - Manrico Balbi; Flavio Scarano; Gian Paolo Bezante (Cardiology Research and Practice)
A 65-year-old man suffering from ascending aorta aneurysm and atherosclerotic three vessel disease without left main involvement underwent aortic root replacement with coronary ostia reimplantation according to the modified Bentall technique and multiple coronary artery bypass grafts. Gelatin-resorcin-formaldehyde glue was used to reinforce the aortic coronary buttons and to facilitate hemostasis. Five months after surgery, the patient experienced rapidly worsening effort angina. Coronary angiography showed severe left main narrowing. The considerable amount of time that elapsed between surgery and the onset of symptoms implies that the problem was not related to an imperfect suture technique, but was most likely caused by an inflammatory and proliferative response to the glue that had been used. We performed elective percutaneous coronary intervention and stenting of the protected coronary vessel without technical difficulties and with a satisfactory final result. The patient is currently symptom-free after 1 year's follow-up.